2007
DOI: 10.1016/j.jaapos.2007.01.119
|View full text |Cite
|
Sign up to set email alerts
|

Monocular activation of V1 and V2 in amblyopic adults measured with functional magnetic resonance imaging

Abstract: Asymmetries in magnitude of monocular activation do occur in subjects with amblyopia, but these basic measures are limited in terms of sensitivity for mild to moderate amblyopia and for specificity between subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 68 publications
11
47
1
Order By: Relevance
“…Initials enclosed by a dashed box indicates responses that are significantly reduced (t-test; P < 0.05) from that of the fellow fixing eye. There is variability across the population with not all amblyopes exhibit reduced magnitude responses for the phase-encoded stimulus, consistent with previous studies [Barnes et al, 2001;Conner et al, 2007a;Li et al, 2007a]. For the population as a whole, the amblyopic response is significantly reduced only in area V1 (T ¼ 2.1993, df ¼ 28; P < 0.05) and Vp (T ¼ 2.1141, df ¼ 28; P < 0.05); however, individual subjects display significant reductions (T > 1.965: P < 0.05, twotailed t-test) in response for the phase-encoded stimulus in all visual areas (e.g., in area V1, ML, HP, SB, YF, HQ, CQ, CW; area V2, WH, CQ, ML, HQ, CW, YF; area V3, ML, SB, ZF, CQ, YF, CW; area Vp, ZF, CQ, HQ, CW, YF; area V3a, WH, CW, CQ, HP, ZF, ML; area V4, HP, HQ; area MT, HQ, HP, CQ.…”
Section: Neural Modelingsupporting
confidence: 88%
“…Initials enclosed by a dashed box indicates responses that are significantly reduced (t-test; P < 0.05) from that of the fellow fixing eye. There is variability across the population with not all amblyopes exhibit reduced magnitude responses for the phase-encoded stimulus, consistent with previous studies [Barnes et al, 2001;Conner et al, 2007a;Li et al, 2007a]. For the population as a whole, the amblyopic response is significantly reduced only in area V1 (T ¼ 2.1993, df ¼ 28; P < 0.05) and Vp (T ¼ 2.1141, df ¼ 28; P < 0.05); however, individual subjects display significant reductions (T > 1.965: P < 0.05, twotailed t-test) in response for the phase-encoded stimulus in all visual areas (e.g., in area V1, ML, HP, SB, YF, HQ, CQ, CW; area V2, WH, CQ, ML, HQ, CW, YF; area V3, ML, SB, ZF, CQ, YF, CW; area Vp, ZF, CQ, HQ, CW, YF; area V3a, WH, CW, CQ, HP, ZF, ML; area V4, HP, HQ; area MT, HQ, HP, CQ.…”
Section: Neural Modelingsupporting
confidence: 88%
“…Our results along with those of [Conner et al, 2007a] do not provide support for the suggestion that V1 and V2 are r Spatial Frequency Deficits in Amblyopia Using fMRI r r 4065 r spared in humans with amblyopia as proposed by [Muckli et al, 2006]. However, in agreement with the results of [Li et al, 2007a], we do find that some individuals exhibit less involvement of V1 and sometimes V2, though this is not a typical finding.…”
Section: Regional Involvementcontrasting
confidence: 76%
“…Others have argued that V1 activation is reduced (Demer et al, 1988;Kabasakal et al, 1995;Goodyear et al, 2000;Barnes et al, 2001;Choi et al, 2001;Algaze et al, 2002;Conner and Mendola, 2005). A number of studies have shown that the extrastriate visual cortex is also affected (Barnes et al, 2001;Conner et al, 2007;Li et al, 2007b). However, to date human brain imaging has not resolved whether the cortical deficit is due to fewer cells, reduced cortical magnification for the AME's input, a disordered projection, or loss of cells' spatial resolution for the AME's input.…”
Section: Introductionmentioning
confidence: 99%